An Unusual Presentation of Primary Hepatic Lymphoma - BS, Pavan; Amina, Nishat; Anand, Rama; Pathania, O.P (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Primary hepatic lymphoma (PHL) is a rare disease that usually manifests as a heterogenous solitary intrahepatic mass, multiple lesions or a diffuse infiltrative form. PHL presenting as a small focal area of hepatic involvement and a large predominant extrahepatic component is uncommon. We report a histopathologically proven case of primary hepatic lymphoma that caused significant diagnostic dilemma on contrast-enhanced computed tomography due to its unusual imaging appearance as a hypo-enhancing intra-abdominal solid mass with relatively small area of hepatic parenchymal involvement and a large exophytic component.
Keywords: primary hepatic lymphoma; exophytic; CECT